2017
DOI: 10.1111/jocd.12329
|View full text |Cite
|
Sign up to set email alerts
|

Review in peeling complications

Abstract: Chemical peeling, a procedure wherein a chemical agent is applied to the skin to cause controlled destruction followed by regeneration and remodeling, is a dynamic tool for the treatment of acne, pigmentation issues, and photoaging [Journal of cutaneous and aesthetic surgery vol. 5 (2012) 254-260]. The results and complications are related to the depth of the procedure, with deeper peels producing more marked results and higher rates of complications. Complications are more likely with darker skin types, certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…SA (2‐hydroxybenzoic acid) is one of the beta‐hydroxy acids used widely in chemical peels and medicaments . Although many topical SA preparations are frequently prescribed, allergic contact dermatitis is uncommon . It has been suggested that cases of contact dermatitis due to salicylates might be overlooked …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SA (2‐hydroxybenzoic acid) is one of the beta‐hydroxy acids used widely in chemical peels and medicaments . Although many topical SA preparations are frequently prescribed, allergic contact dermatitis is uncommon . It has been suggested that cases of contact dermatitis due to salicylates might be overlooked …”
Section: Discussionmentioning
confidence: 99%
“…Although chemical peeling is a safe procedure for the treatment of many dermatological conditions, some complications have been described . Cases of contact urticaria (CU) caused by chemical peels have rarely been reported …”
mentioning
confidence: 99%
“…Complications that are common a few days or weeks following the procedure for every type of agent, include swelling, erythema, pain and burning, pruritus, ecchymoses, blistering or infection, milia, and telangiectasia. 11 , 38 , 57 Some patients may develop skin textural changes and appearance of enlarged pores. 11 These complications are usually mild and resolve within weeks but tend to be more serious for deep peels.…”
Section: Peeling Complicationsmentioning
confidence: 99%
“… 7 Superficial peels are most commonly used for mild skin disorders such as dyschromia, acne, postinflammatory hyperpigmentation, melasma, and actinic keratosis. 8 , 11 Medium depth peels are used for solar keratoses or lentigines, pigmentary disorders, and superficial scars. Deep chemical peels are used for the treatment for photoaging, deep scars or wrinkles, and precancerous skin lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent erythema, swelling, pain, allergic reactions, herpes recurrence, acne, dyspigmentation, etc. are some of the various after effects associated with treatment strategies like chemical peeling, dermabrasion, laser therapy, and cosmetic camouflage [50,51].…”
Section: Consequences Of Conventional Treatment Strategiesmentioning
confidence: 99%